RICE : 80+ NICE RICE RECIPES FROM ASIA - Hayes, Avery (Naarm (Melbourne), Australia : Smith Street Books, 2024)
A collection of the best dishes of the rice world, from Sushi to Biryani to Bibimbap. With 80 delicious recipes, beautiful photography, and dishes that are as simple as they're packed with flavour, this book is (almost) as good as a trip across Asia. Each chapter features a different style of rice-steamed, fried, simmered, molded, and sweet forming the base for some very good recipes. From the staples you've loved for years to contemporary creations that will have you cooking them again and again, Rice's recipes include congee, onigiri, nasi lemak, Hainanese chicken and sticky rice with coconut caramel and sesame. With recipes for basics and plenty of vegetarian and vegan-friendly options, there's no reason to ever stop eating this delicious grain.
Includes index
Keywords: Cooking (Rice); Rice; Cooking, Asian